On the dynamics of wind-driven circumpolar currents - Tansley, C; Marshall, D (2001)
The factors controlling the transport of the Antarctic Circumpolar Current (ACC) have recently been a topic of heated debate. At the latitudes of Drake Passage, potential vorticity contours are uninterrupted by coastlines, and large amplitude flows are possible even with weak forcing and dissipation. The relationship between the dynamics of circumpolar currents and inertial recirculations in closed basins is discussed. In previous studies, Sverdrup balance and baroclinic adjustment theories have both been proposed as theories of the ACC transport. These theories predict the circumpolar transport as various simple functions of the surface wind stress. A series of experiments is performed with a simple channel model, with different wind strengths and different idealized basin geometries, to investigate the relationship between wind strenght and circumpolar transport. The results show that baroclinic adjustment theories do predict transport in the special case of a periodic channel with no topographic variations, or when the wind forcing is very weak. More generally, the transport is determined by a complex interplay between wind forcing, eddy fluxes, and topographic effects. There is no support for the idea that Sverdrup balance determines the transport through Drake Passage.